ASSESSMENT OF DOSE FOR CHEST X-RAY EXAMINATION AT STATE SPECIALIST HOSPITAL GOMBE (SSHG) AND FEDERAL TEACHING - SEYDOU, HANKOURAOU; KAWU, ABDULSALAM AHMED (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2020)
Assessment of dose for chest x-ray examination is of great value in radiation protection field. This study was carried out in two hospitals in Gombe, Gombe State Nigeria. The aim and objective of this work was to assess the Entrance Skin Dose delivered to patients during routine chest x-ray examination and the Effective dose. A total of forty-two (42) Thermoluminescent Dosimeters (TLD) were placed on the patients during chest x-ray exposure to estimate the Entrance Skin Dose received by patients of different ages and heights. The irradiated TLD chips used were read with a Hashaw 45100 TLD reader available at the Centre for Energy Research and Training (CERT), Ahmadu Bello University, Zaria. The ESDs and EDs were obtained using six approaches: Thermoluminescence Dosimeter (TLDs) chips, Edwin & McCullough’s formula, Edmond’s formula, Kumar et al.’s formula, Chougule & Hussaini’s formula and Pratik et al.’s formula. The ESD result shows that the mean doses obtained in the two hospitals were 0.33 ± 0.04 mGy and 0.35 ± 0.07 mGy for SSHG and FTHG respectively. While the mean ED results were 0.04 ± 0.002 mSv and 0.04 ± 0.004 mSv for SSHG and FTHG respectively. The results obtained were slightly higher compared to other established work.